Diversity of microorganisms in Hyalomma aegyptium collected fromspur-thighedtortoise(Testudograeca)in North Africa and Anatolia - Norte, A.C. (2021)
Ticks carry a diverse community of microorganisms including non-pathogenic symbionts, commensals, and pathogens, such as viruses, bacteria, protozoans, and fungi. The assessment of tick-borne microorganisms (TBM) in tortoises and their ticks is essential to understand their eco-epidemiology, and to map and monitor potential pathogenstohumansandotheranimals.Theaimofthisstudywastocharacterizethe diversity of microorganisms found in ticks collected from the spur-thighed tortoise (Testudo graeca) in North Africa and Anatolia. Ticks feeding on wild T. graeca were collected, and pathogens were screened by polymerase chain reaction using groupspecific primers. In total, 131 adult Hyalomma aegyptium ticks were collected from 92 T. graeca in Morocco (n = 48), Tunisia (n = 2), Algeria (n = 70), and Turkey (n = 11). Bacteria and protozoa detected included Hemolivia mauritanica (22.9%), Midichloria mitochondrii (11.4%), relapsing-fever borreliae (8.4%), Ehrlichia spp. (7.6%), Rickettsia spp. (3.4%), Borrelia burgdorferi s.l. (0.9%), Francisella spp. (0.9%), and Wolbachia spp. (0.8%). The characterization of Rickettsia included R. sibirica mongolitimonae (Algeria), R. aeschlimannii (Turkey), and R.africae (Morocco). Hemolivia mauritanica and Ehrlichia spp. prevalence varied significantly with the sampling region/country. We did not detect significant associations in microorganism presence within ticks, nor between microorganism presence and tick mitochondrial DNA haplogroups. This is the first report of Francisella persica-like, relapsing fever borreliae, M. mitochondrii, andWolbachia spp. in H.aegyptiumticks collected from wild hosts from the South and Eastern Mediterranean region, and of R. sibirica mongolitimonae and R. africae in H. aegyptium from Algeria and Morocco, respectively. Given that T. graeca is a common species in commercial and non-commercial pet trade, the evaluation of the role of this species anditsticksashostsforTBMisparticularlyrelevantforpublichealth